2015
DOI: 10.1086/679628
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenous Waste Handling by Larval ZebrafishDanio rerioin Alkaline Water

Abstract: Although adult fish excrete their nitrogenous waste primarily as ammonia, larval fish may excrete a higher proportion as urea, an evolutionary strategy that lessens nitrogenous waste toxicity during early development. Previous studies firmly established that ammonia excretion is inhibited in adult fish acutely exposed to alkaline water. This study was designed to test the hypothesis that total nitrogen excretion is maintained in larval zebrafish raised in alkaline water (pH ∼ 10.0) as a result of compensatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The up‐regulation of L‐glutamic acid in zebrafish embryos exposed to 300 μg/L triclosan embryos in the present study may be related to a change in the gamma‐aminobutyric acid system, which also reflects damage in brain development (Santos‐Fandila et al ). This is consistent with previous studies showing that cholinesterase activity can be significantly elevated in zebrafish exposed to triclosan (Oliveira et al ) and that triclosan‐exposed zebrafish exhibit gene expression changes in the brain and apoptosis in neuronal cells (Kumai et al ; Szychowski et al ). However, the results of one study have conversely demonstrated that triclosan is a very weak nonneurotoxin (Muth‐Kohne et al ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The up‐regulation of L‐glutamic acid in zebrafish embryos exposed to 300 μg/L triclosan embryos in the present study may be related to a change in the gamma‐aminobutyric acid system, which also reflects damage in brain development (Santos‐Fandila et al ). This is consistent with previous studies showing that cholinesterase activity can be significantly elevated in zebrafish exposed to triclosan (Oliveira et al ) and that triclosan‐exposed zebrafish exhibit gene expression changes in the brain and apoptosis in neuronal cells (Kumai et al ; Szychowski et al ). However, the results of one study have conversely demonstrated that triclosan is a very weak nonneurotoxin (Muth‐Kohne et al ).…”
Section: Discussionsupporting
confidence: 92%
“…The generation of urea provides insight into fish nitrogen balance and has been reported to be a useful marker for environmental stress in fish. Although adult fish mainly excrete their nitrogenous waste as ammonia, zebrafish embryos and larvae excrete approximately 80% of nitrogenous waste as urea, using the urea transporters as a tool to efficiently cross plasma membranes (Braun et al , ; Kumai et al ). In the present study, we observed increased urea levels in zebrafish embryos exposed to triclosan.…”
Section: Discussionmentioning
confidence: 99%
“…NH 4 + and HCO 3 − can be used to produce urea in the liver for acid–base homeostasis (Weiner and Verlander 2016 ). Upregulation of Tgm5 probably takes effect by promoting NH4 + transportation as glutamine after NH 3 incorporation to achieve acid–base homeostasis (Kumai, et al 2015 ; Wang, et al 2003 ; Yao, et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in embryos, ammonia excretion is limited by the chorion so fish must detoxify ammonia by synthesizing urea [36,37]. All this similarities with mammals could be an indication of how zebrafish embryos could be used as a model to study the nanoparticles capacity to retain ammonia [38,39].…”
Section: Discussionmentioning
confidence: 99%